Empowering MSME Through Digital Marketing and Product Branding in Tugu Selatan Village, Cisarua, Bogor - Sya’banniah, Nispi Yani; Gemina, Dwi; Setiawan, Ade Budi; Septiani, Imas Noer; Sukamto, Muhamad Fadel (Jurnal Pengabdian Masyarakat Formosa, 2023)
Community empowerment is an activity to increase community participation in fulfilling life needs and solving problems experienced by the community. This community service was carried out in Tugu Selatan Village, Cisarua District, Bogor Regency. This activity aims to empower MSMEs and provide knowledge and training to business actors in increasing competitiveness in this era of globalization. Because currently the economic conditions have followed the times that all use digital in their business, but many MSMEs do not take advantage of it. The problem faced by these MSMEs is that there is no utilization of digital marketing in promoting their products and no implementation of product branding, and digital marketing training, making social media accounts, and making packaging brand labels are expected to help MSMEs in introducing their products to consumers to increase their competitiveness so that marketing can be done effectively and efficiently.